Cataract surgical quality and cost in a hill region of Western Nepal: comparing outreach eye camps with base hospital - Laxmi Devi Manandhar; Salma KC Rai; Kabindra Bajracharya; Ram Prasad Kandel; Prasanna Sharna; Ken Bassett (Asian Journal of Medical Sciences, 2018)
Background: Base hospitals that provide cataract surgical services in outreach settings need evidence that the cataract surgical quality is maintained in the camp setting and that patients achieve cost savings.